Nutrition education in Southeast Sulawesi Province, Indonesia: A cluster randomized controlled study - Devi Savitri Effendy; Pattaneeya Prangthip; Ngamphol Soonthornworasiri; Pattanee Winichagoon; Karunee Kwanbunjan (Wiley, 2020)
Abstract This study evaluated the impact of a nutrition education intervention on child feeding practices and children's nutritional status. Using a randomized controlled trial, we conducted an intervention for 6 months among caregivers with children aged 6-17 months in two subdistricts of Kendari, SE Sulawesi Province, Indonesia. In all, 22 integrated health posts were randomly assigned to an educational intervention or control group with 266 participants in both groups. Participants in the intervention group attended four nutrition classes and received a monthly home visit by cadres (community volunteers), whereas participants in the control group only received standard monthly health care at the health post. The primary study outcome was children's dietary diversity scores (DDSs). Mixed model analysis was conducted to examine the intervention effects on DDS and children's growth adjusting for clustering within subvillages. The study showed the educational intervention had a significant effect on children's DDS. Children in the intervention group had a larger DDS compared with children in the control group (Beta [mean difference] = 0.34, 95% CI: 0.02 to 0.66, P = 0.038). The intervention effect on height‐for‐age z‐score (HAZ) could not be shown (Beta = 0.24, 95% CI: −0.06 to 0.56, P = 0.112). However, stunting prevalence remained stable in the intervention group but increased in the control group. These results indicated nutrition education delivered through nutrition classes combined with regular home visits by cadres as influencers provided a great potential to be adopted to complement other nutrition programmes in community health centres.